Time management - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. ; [production company] ; Kuala Lumpur : First Training [distributor])
Described the type of time management. How the manager doing a time management.
Copy available in DVD format
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Time management